Corrosion inhibition of carbon steel in perchloric acid by potassium iodide - Attar, Tarik; Benchadli, Abbes; Choukchou-Braham, Esma (International Journal of Advanced Chemistry, 2019)
Corrosion processes are responsible for numerous losses mainly in the industrial scope. It is clear that the best way to combat it is pre-vention. The effect of temperature on the corrosion behavior of carbon steel was studied by mass loss measurements in the temperature range 293â€“333 K. The inhibition efficiency increases with increasing temperature. The inhibitor showed 97.98 % inhibition efficiency at 1.10-3 M concentration of iodide potassium in 1 M perchloric acid solutions. The values of activation energy (Ea), enthalpy of activation (Î”Ha) and entropy of activation (Î”Sa), free energy of adsorption (Î”Gads), enthalpy of adsorption (Î”Hads) and entropy of adsorption (Î”Sads) were calculated. The adsorption of this inhibitor on carbon steel surface obeys Langmuir adsorption isotherm.Â Â